Hand Washing Education Using Video Animation to Enhance Knowledge and Attitudes among Secondary School Students: A Quasi-Experimental Study - Kusbaryanto Kusbaryanto; Ellentisa Natan Dwitasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hand hygiene represents a fundamental infection prevention strategy, particularly critical among adolescent populations who serve as potential vectors for respiratory and gastrointestinal disease transmission. This study aimed to evaluate the efficacy of animated video-based educational interventions on hand hygiene knowledge and attitudinal outcomes among junior high school students. A quasi-experimental pre-test/post-test design without control group was implemented among 109 seventh-grade students at one public Secondary High School (SHS) in Bantul, Indonesia. Convenience sampling was employed across five class sections. Participants received a structured educational intervention utilizing animated video content. Assessment was conducted via validated knowledge and attitude questionnaires administered before and after intervention. Statistical analysis employed the Wilcoxon signed-rank test to evaluate intervention effects. Participants (58.7% female, 41.3% male) demonstrated statistically significant improvement in hand hygiene knowledge scores following the intervention (pre-test mean=9.55±0.687; post-test mean=9.76±0.507; p=0.001). However, attitudinal measures did not show significant change (pre-test mean=30.68±4.86; post-test mean=31.35±4.76; p=0.160). Animated video-based educational interventions demonstrate significant efficacy in enhancing hand hygiene knowledge among secondary school students, though attitudinal changes appear more resistant to short-term intervention.